P0299EVALUATION OF THE CORRELATION BETWEEN VITAMIN D LEVELS AND THROMBOCYTE MARKERS IN PATIENTS WITH DİALYSİS, CHRONIC RENAL DISEASE AND RENAL TRANSPLANTATION PATIENTS. (6th June 2020) - AHMEDOVA, KÖNÜL; SAHIN, Garip; Bal, Cengiz; Mutluay, Rüya
Abstract: Background and Aims: 25(OH)D3 levels are known to be lower in patients with chronic renal disease (CRD). Vitamin D supplementation has been shown to have beneficial effects on mortality in these patients. In our study, we have evaluated the pleiotropic effect of vitamin D on thrombocyte markers, which is known very little by most. Method: The main thrombocyte function markers (MPV, PDW and PCT) were obtained in patients which underwent dialysis, renal transplantation and patients with grade 3-4 CRD before and after vitamin D supplementation. 40 healthy individuals were chosen as control group and 24 patients underwent renal transplantation, 25 patients underwent dialysis for at least 3 months, 32 patients were diagnosed as Grade 3-4 CRD. All of the patients above had 25(OH)D3 levels <20ng/mL (<50nmol/L). Thrombocyte markers were evaluated before and after vitamin D supplementation (which was given 50.000 IU orally once a week for 8 weeks). Results: Statistically no significant difference were found between MPV values in- and across- group comparison before and after vitamin D supplementation. After the correlation analyses were reviewed, statistically significant negative correlation was found (r=-0, 422 p<0.05) between ΔMPV and ΔVitamin D in renal transplantation group. Also statistically significant positive correlation was found between ΔPDW and ΔVitamin D. In the control group with healty participants, a statistically significant negative correlation was found (r=-0, 493 p<0.05) between ΔVitamin D and ΔThrombocyte count. In the dialysis group a statistically significant negative correlation was found (r=-0, 422 p<0.05) between ΔVitamin D and ΔMPV. Conclusion: A significant correlation was found particularly between Vitamin D and MPV in dialysis and renal transplantation patients. In order to prevent cardiovascular events due to thrombosis caused by Vitamin D deficiency which increases MPV, it has been thought that Vitamin D supplementation and antiaggregant therapy might be beneficial.